Complex gastroschisis: a new indication for fetal surgery?. (1st December 2021) - Joyeux, L.; Belfort, M. A.; De Coppi, P.; Basurto, D.; Valenzuela, I.; King, A.; De Catte, L.; Shamshirsaz, A. A.; Deprest, J.; Keswani, S. G.
ABSTRACT: Gastroschisis (GS) is a congenital abdominal wall defect, in which the bowel eviscerates from the abdominal cavity. It is a non‐lethal isolated anomaly and its pathogenesis is hypothesized to occur as a result of two hits: primary rupture of the 'physiological' umbilical hernia (congenital anomaly) followed by progressive damage of the eviscerated bowel (secondary injury). The second hit is thought to be caused by a combination of mesenteric ischemia from constriction in the abdominal wall defect and prolonged amniotic fluid exposure with resultant inflammatory damage, which eventually leads to bowel dysfunction and complications. GS can be classified as either simple or complex, with the latter being complicated by a combination of intestinal atresia, stenosis, perforation, volvulus and/or necrosis. Complex GS requires multiple neonatal surgeries and is associated with significantly greater postnatal morbidity and mortality than is simple GS. The intrauterine reduction of the eviscerated bowel before irreversible damage occurs and subsequent defect closure may diminish or potentially prevent the bowel damage and other fetal and neonatal complications associated with this condition. Serial prenatal amnioexchange has been studied in cases with GS as a potential intervention but never adopted because of its unproven benefit in terms of survival and bowel and lung function. We believe that recent advances in prenatal diagnosis and fetoscopic surgery justify reconsideration of the antenatal management of complex GS under the rubric of the criteria for fetal surgery established by the International Fetal Medicine and Surgery Society (IFMSS). Herein, we discuss how conditions for fetoscopic repair of complex GS might be favorable according to the IFMSS criteria, including an established natural history, an accurate prenatal diagnosis, absence of fully effective perinatal treatment due to prolonged need for neonatal intensive care, experimental evidence for fetoscopic repair and maternal and fetal safety of fetoscopy in expert fetal centers. Finally, we propose a research agenda that will help overcome barriers to progress and provide a pathway toward clinical implementation. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Revisión de técnicas de vanguardia La gastrosquisis (GS) es un defecto congénito de la pared abdominal, en el que el intestino se eviscera de la cavidad abdominal. Se trata de una anomalía aislada no letal y se hipotetiza que su patogénesis se produce como resultado de dos daños: rotura primaria de la hernia umbilical 'fisiológica' (anomalía congénita) seguida de un daño progresivo del intestino eviscerado (lesión secundaria). Se cree que el segundo daño está causado por una combinación de isquemia mesentérica causada por la constricción en el defecto de la pared abdominal y la exposición prolongada al líquido amniótico, con el consiguiente daño inflamatorio, que finalmente conduce a la disfunción intestinal y a otras complicaciones. La GS puede clasificarse como simple o compleja, pudiéndose complicar esta última por una combinación de atresia intestinal, estenosis, perforación, vólvulo y/o necrosis. La GS compleja requiere múltiples operaciones de cirugía al recién nacido y está asociada a una morbilidad y mortalidad postnatal significativamente mayor que la GS simple. La reducción intrauterina del intestino eviscerado antes de que se produzca un daño irreversible y el posterior cierre del defecto pueden disminuir o incluso prevenir el daño intestinal y otras complicaciones fetales y neonatales asociadas a esta condición. El intercambio amniótico prenatal en serie se ha estudiado en casos con GS como una posible intervención, pero nunca se ha adoptado debido a que su beneficio no ha sido probado en términos de supervivencia y de la función intestinal y pulmonar. Se cree que los recientes avances en el diagnóstico prenatal y la cirugía fetoscópica justifican reconsiderar el tratamiento prenatal de la GS compleja en función de los criterios de cirugía fetal establecidos por la Sociedad Internacional de Medicina y Cirugía Fetal (IFMSS, por sus siglas en inglés). En este artículo se discuten las condiciones para la reparación fetoscópica de la GS compleja que podrían ser favorables según los criterios de la IFMSS, como la existencia de un historial médico, un diagnóstico prenatal preciso, la ausencia de un tratamiento perinatal totalmente eficaz debido a la necesidad de cuidados intensivos neonatales prolongados, la evidencia experimental sobre la reparación fetoscópica, y la seguridad materna y del feto de la fetoscopia en centros especializados en medicina fetal. Por último, se propone un programa de investigación que ayudará a superar las barreras ante futuros avances y proporcionará una vía para la implementación clínica. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. 摘要: 当前发展状况评述 腹裂(GS)是一种先天性腹壁缺损，其中肠管自腹腔中脱出。它是一种非致命的单纯性畸形，其发病机理被假设为两次破环的结果:首先是"生理性"脐疝的原发性破裂(先天性异常)，随后是脱出肠管的渐进性损伤(继发性损伤)。第二次破坏被认为是由腹壁缺损收缩引起的肠系膜缺血和羊水长时间暴露导致炎症损伤的组合引起的，最终导致肠道功能障碍和并发症。GS可分为单纯或复杂，后者因结合肠闭锁、狭窄、穿孔、肠扭转和/或坏死而复杂化。复杂的GS需要多次新生儿手术，并且与单纯的GS相比，出生后发病率和死亡率明显更高。在发生不可逆转的损伤和随后的缺损闭合之前，宫内脱出内脏的肠腔可能减少或潜在地防止肠损伤以及与这种病情相关的其他胎儿和新生儿并发症。连续产前羊膜置换作为一种潜在的干预措施已经在GS病例中得到了研究，但从未被采用，这是因为它在存活、肠和肺功能方面的益处未经证实。我们认为，产前诊断和胎儿镜手术的最新进展证明，在国际胎儿医学和外科学会 (IFMSS) 制定的胎儿手术标准的说明下重新考虑复杂GS的产前管理是合理的。在此，我们讨论了根据IFMSS标准，胎儿镜修复复杂GS的病情如何可能是有利的，包括确立的自然病史、准确的产前诊断、由于长时间需要新生儿重症监护而缺乏完全有效的围产期治疗，以及在专家胎儿中心进行胎儿镜修复和胎儿镜检查的母婴安全的实验证据。最后，我们提出了一个研究议程，这将有助于克服阻挡进步的障碍，并提供一条通往临床实施的途径。© 2021年国际妇产科超声学会。